2011
DOI: 10.1016/j.bpc.2011.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Predicting nucleosome positioning in genomes: Physical and bioinformatic approaches

Abstract: In eukaryotic genomes, nucleosomes are responsible for packaging DNA and controlling gene expression. For this reason, an increasing interest is arising on computational methods capable of predicting the nucleosome positioning along genomes. In this review we describe and compare bioinformatic and physical approaches adopted to predict nucleosome occupancy along genomes. Computational analyses attempt at decoding the experimental nucleosome maps of genomes in terms of certain dinucleotide step periodicity obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 79 publications
(137 reference statements)
0
5
0
Order By: Relevance
“…Indeed, the sequence-directed nucleosome positioning is directly observed from in vitro data, because chromatin is reconstituted from DNA and histones only, without any other external factors such as remodelers found in vivo. Accordingly, models established from in vitro genome-wide reconstitution of chromatin predict rather well in vivo nucleosome positioning [22,53,[55][56][57][58][59][60], corroborating the hypothesis that the DNA sequence plays a major role among the different factors influencing the position of nucleosomes [61]. During the past 40 years, attempts to describe the sequence-directed nucleosomal positioning showed that one needs to consider two types of mechanisms (Figure 1): (i) positioning mechanisms where DNA motifs at specific location accommodate DNA wrapping in the nucleosome, for example by favoring certain dinucleotides at contact points between DNA and histones; and (ii) inhibiting mechanisms, with sequences such as poly(dA:dT) preventing nucleosome formation [1].…”
Section: How Is Nucleosome Positioning Encoded In the Dna Sequence? 21 Dna Sequence Does Influence Nucleosome Positioningmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, the sequence-directed nucleosome positioning is directly observed from in vitro data, because chromatin is reconstituted from DNA and histones only, without any other external factors such as remodelers found in vivo. Accordingly, models established from in vitro genome-wide reconstitution of chromatin predict rather well in vivo nucleosome positioning [22,53,[55][56][57][58][59][60], corroborating the hypothesis that the DNA sequence plays a major role among the different factors influencing the position of nucleosomes [61]. During the past 40 years, attempts to describe the sequence-directed nucleosomal positioning showed that one needs to consider two types of mechanisms (Figure 1): (i) positioning mechanisms where DNA motifs at specific location accommodate DNA wrapping in the nucleosome, for example by favoring certain dinucleotides at contact points between DNA and histones; and (ii) inhibiting mechanisms, with sequences such as poly(dA:dT) preventing nucleosome formation [1].…”
Section: How Is Nucleosome Positioning Encoded In the Dna Sequence? 21 Dna Sequence Does Influence Nucleosome Positioningmentioning
confidence: 99%
“…Nucleosome occupancy encoded in the sequence can presumably be predicted through sequence-based modeling. This was achieved using mainly two types of approaches: bioinformatic models relying on machine learning [22,53,56,58], and physical models relying on energy calculations [55,57,59,60,77]. The general idea of the bioinformatic models is to detect, genome-wide, the sequence features associated with nucleosomal positioning.…”
Section: Predicting Nucleosomal Positioning From Sequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, experimental mapping of genome-wide nucleosome organization has been obtained for several model systems 33 34 35 36 37 38 , such as Saccharomyces cerevisiae , Caenorhabditis elegans , Drosophila melanogaster and Homo sapiens , but the mechanism of nucleosome positioning still remains elusive. A variety of models have been proposed for predicting nucleosome occupancy that are classified into categories of bioinformatics 19 39 40 41 42 43 44 45 and energetics of nucleosomal DNA 46 47 48 49 50 51 52 53 54 . Bioinformatics models learn various sequence features, such as dinucleotide distributions and oligonucleotide motif frequency from a large quantity of nucleosomes 39 40 41 42 43 .…”
mentioning
confidence: 99%
“…There are a number of energetics models designed to predict nucleosome formation energy, nucleosome occupancy and positions 46 47 48 49 50 51 52 53 54 . A model 51 that took into account the deformations of DNA helical twist, roll and tilt achieved a moderate correlation between its prediction and experimental nucleosome occupancy (R = 0.45, P < 0.0001, on yeast chromosome III).…”
mentioning
confidence: 99%